Preliminary characterization of the self-incompatibility genotypes of European plum (Prunus domestica L.) cultivars - Halász, J.; Kurilla, A.; Hegedűs, A. (International Journal of Horticultural Science, 2014)
European plum is an important fruit crop with complex, hexaploid genome of unknown origin. The characterization of the selfincompatibility (S) locus of 16 European plum cultivars was carried out using the PaConsI-F primer in combination with the EM-PC1consRD primer for the first intron and the EM-PC2consFD and EM-PC3consRD primers for the second intron amplification. Altogether, 18 different alleles were scored indicating high genetic diversity. These alleles were labelled using alphabetical codes from SA to SS. We identified 5 different alleles in 9 cultivars, 4 alleles in 5 cultivars, while 3 alleles were shown in two of the assayed cultivars. A total of 16 different S-genotypes were assigned, and discrimination of all plum cultivars was successful based on their unique S-genotypes. However, further research is required to reliably identify the S-alleles based on their DNA sequence and clarify complete S-genotypes.